Person-attuned musical interactions (PAMI) in dementia care. Complex intervention research for constructing a training manual - Ridder, Hanne Mette; Krøier, Julie Kolbe; Anderson-Ingstrup, Jens; McDermott, Orii (Frontiers in Medicine, 2023)
Introduction Music is of vital importance for cognition, human care, and the formation of social communities throughout life. Dementia is a neurocognitive disorder that affects cognitive domains, and in late-stage dementia, care is needed in all aspects of daily living. Within residential care home contexts, carers play a significant role for the “caring culture” but often lack professional training in verbal and non-verbal communication skills. Thus, there is a need for training carers to respond to the multidimensional needs of persons with dementia. Music therapists use musical interactions but are not trained to train carers. Therefore, our aim was to explore person-attuned musical interactions (PAMI), and additionally, to develop and evaluate a training manual to be used by music therapists when supporting and training carers in non-verbal communication with persons with late-stage dementia in residential care home contexts. Research process With a realist perspective and systems thinking and within the framework for complex intervention research, the research group integrated several overlapping subprojects by applying a non-linear and iterative research process. Core elements related to person-centered dementia care as well as learning objectives were considered through the following four phases; Developing, Feasibility, Evaluation, and Implementation. Results The result was a training manual for qualified music therapists to use when teaching and collaborating with carers about how to implement PAMI in dementia care. The manual included comprehensive resources, a clear structure for training, defined learning objectives, and integration of theory. Discussion With increased knowledge about caring values and non-verbal communication, residential care home cultures may develop carer competencies and provide professional attuned care for persons with dementia. Further piloting and testing to examine the general effect on caring cultures is needed.